Variation in Seed Allergen Content From Three Varieties of Soybean Cultivated in Nine Different Locations in Iowa, Illinois, and Indiana - McClain, Scott; Stevenson, Severin E.; Brownie, Cavell; Herouet-Guicheney, Corinne; Herman, Rod A.; Ladics, Gregory S.; Privalle, Laura; Ward, Jason M.; Doerrer, Nancy; Thelen, Jay J. (Frontiers in Plant Science, 2018)
Soybean (Glycine max) is an important food stock, and also considered an allergenic food with at least eight well characterized allergens. However, it is a less prevalent allergen source than many other foods and is rarely life-threatening. Soybean is incorporated into commonly consumed foods, and therefore, the allergens pose a potential concern for individuals already sensitized. The protein profile of soybean can be affected by several factors including genetic, environmental. To investigate how soybean allergen content may be affected by genetics and/or environment, nine soy allergens were quantified from three commercial soybean varieties grown at nine locations in three states within a single climate zone in North America; Iowa, Illinois, and Indiana, USA. Quantification was achieved using liquid chromatography-selected reaction monitoring tandem mass spectrometry (LC-SRM) with AQUA peptide standards specific to the nine target allergens. Quantitation of allergen concentration indicated that both genetics and location affected specific allergen content. Seven of the nine allergens were significantly influenced by genetics; with the exceptions of glycinin G4 and KTI 3. The allergens P34, Gly m Bd 28k, glycinin G3 and KTI 1 showed statistically significant impact from location as well, but at a lower threshold of significance compared with genetics (cultivar/variety). This dataset contributes to our understanding of the natural variation of endogenous allergens, as it represents a sampling of soybeans grown in a controlled, distributed plot design under agronomic conditions common for commercial soybean food and feed production. The aim was to build upon our recent understanding of how allergens are expressed as part of the overall soybean proteome.